Absence of transforming growth factor-beta type II receptor is associated with poorer prognosis in HER2-negative breast tumours - Paiva, C. E. [UNESP]; Linde, Sandra Aparecida Drigo [UNESP]; Rosa, F. E. [UNESP]; Neto, F. A. Moraes; Caldeira, Jose R. F. [UNESP]; Soares, F. A.; Domingues, Maria Aparecida Custódio [UNESP]; Rogatto, Silvia Regina [UNESP] (Oxford University Press, 2010)
Background: The clinical relevance of transforming growth factor-beta (TGF-beta)-signalling pathway in breast carcinomas (BCs) remained elusive. This study aimed to evaluate the prognostic value of TGF-beta and transforming growth factor-beta type II receptor (TGF-beta RII) expression levels in tumour cells and their association with the established biomarkers in BC.Patients and methods: In 324 BC from patients with long-term follow-up, the TGF-beta 1 and TGF-beta RII transcript and protein expression levels were assessed.Results: TGF-beta 1 and TGF-beta RII down-expression was significantly associated with BC. Negative TGF-beta 1 and TGF-beta RII protein status was associated with the development of distant metastasis (P = 0.003 and P = 0.029, respectively). In multivariate analysis, TGF-beta 1-positive tumours were associated with increased disease-free survival (DFS) [hazard ratio (HR) = 0.489, P = 0.003]. TGF-beta RII positivity was an independent prognostic factor for DFS (HR = 0.439, P = 0.001) and overall survival (OS) (HR = 0.409, P = 0.003) in human epidermal growth factor receptor2 (HER2)-negative patients. Absence of TGF-beta 1 and TGF-beta RII proteins in breast tumour cells was significantly associated with metastasis development.Conclusions: To the best of our knowledge, this is the first report indicating the relevance of HER2 status in discriminating TGF-beta RII as a prognostic marker for DFS and OS in human BC. These data indicate that TGF-beta RII protein analysis in tumour cells could be introduced in clinical practice as additional prognostic biomarker in HER2-negative BC.
Keywords: breast cancer; HER2; prognostic markers; TGF-beta 1; TGF-beta RII